PENGARUH KARAKTERISTIK KOMITE AUDIT, FUNGSI AUDIT INTERNAL DAN KUALITAS AUDIT TERHADAP PENGUNGKAPAN SUKARELA: THE EFFECT OF THE CHARACTERISTICS OF THE AUDIT COMMITTEE, THE FUNCTION OF INTERNAL AUDIT, AND THE QUALITY OF AUDIT ON VOLUNTARY DISCLOSURE - Felisitas Nicko; Petrus Ridaryanto; Renato Sitompul (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2022)
The aim of this study is to build empirical evidence that audit committee composition, internal audit function, and audit quality all have an impact on voluntary disclosure. Data in this study was collected from manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2015 to 2019. In this study, samples were determined using purposive sampling techniques with criteria tailored to data requirements. After sampling, the total number of samples was 150. To reduce data bias, the data analysis method first used Ordinary Least Squares (OLS) along with the classical assumption test procedure. The findings show that the characteristics of the audit committee, internal audit function, and audit quality have a positive effect on voluntary disclosure.